Shoulder Injuries in English Community Rugby Union - Singh, V. R.; Trewartha, G.; Roberts, S. P.; England, M.; Stokes, K. A. (International Journal of Sports Medicine, 2016)
The aim of this study was to describe the incidence, severity and type of shoulder injuries resulting from match play in adult community rugby union between 2009–2013. A total of 254 time-loss shoulder injuries were reported, an overall incidence of 2.2 per 1 000 h (95% CI: 1.9 to 2.4), and a mean injury severity of 9.5 weeks missed (95% CI: 8.2 to 10.8). The semi-professional group had an incidence of 2.8 injuries per 1 000 h (95% CI: 2.2 to 3.5), which was higher than the recreational group at 1.8 injuries per 1 000 h (95% CI: 1.4 to 2.2, p=0.004). The incidence of acromioclavicular joint injury for semi-professional players was 1.2 per 1 000 h (95% CI: 0.8 to 1.6); which was significantly higher than the incidence of this injury type in recreational players (0.5 per 1 000 h 95% CI: 0.3 to 0.7, p=0.002). Overall, back row players sustained the highest incidence of all shoulder injuries for a given playing position, 2.9 injuries per 1 000 h (95% CI: 2.2 to 3.6). The tackle was the main event associated with injury. Injury prevention programs and coaching strategies that consider tackle technique and physical conditioning of the shoulder region are therefore considered important.
Keywords: acromioclavicular; injury epidemiology; sport; tackle; time-loss